Measuring the performance of insurance industry in Malaysia: Islamic vis-à-vis conventional insurance - Abduh, Muhamad; Omar, Mohd. Azmi; Mohd Tarmizi, Raudhah (2012)
The development of Islamic financial institutions is growing tremendously since the last three decades. However, many studies are focused more on the development and performance of banking and other financial markets and almost neglecting another specific and important sector, which is insurance. Thus, this study aims to measure the performance of Islamic insurance industry in Malaysia and compares them with their conventional counterpart. This study covers a three-year period, i.e. 2008 to 2010 and employs ratio analysis and data envelopment analysis to measure the performance of both industries. The findings show that insurance industry is more efficient than Takaful industry in both ratio analysis and data envelopment analysis.